Evolution of Quality Assurance for Clinical Immunohistochemistry in the Era of Precision Medicine: Part 1. Issue 1 (January 2017) - Cheung, Carol C.; D'Arrigo, Corrado; Dietel, Manfred; Francis, Glenn D.; Gilks, C. Blake; Hall, Jacqueline A.; Hornick, Jason L.; Ibrahim, Merdol; Marchetti, Antonio; Miller, Keith; van Krieken, J. Han; Nielsen, Soren; et al.
Abstract : Technical progress in immunohistochemistry (IHC) as well as the increased utility of IHC for biomarker testing in precision medicine avails us of the opportunity to reassess clinical IHC as a laboratory test and its proper characterization as a special type of immunoassay. IHC, as used in current clinical applications, is a descriptive, qualitative, cell-based, usually nonlinear, in situ protein immunoassay, for which the readout of the results is principally performed by pathologists rather than by the instruments on which the immunoassay is performed. This modus operandi is in contrast to other assays where the instrument also performs the readout of the test result (eg, nephelometry readers, mass spectrometry readers, etc.). The readouts (results) of IHC tests are used either by pathologists for diagnostic purposes or by treating physicians (eg, oncologists) for patient management decisions, the need for further testing, or follow-up. This paper highlights the distinction between the original purpose for which an IHC test is developed and its subsequent clinical uses, as well as the role of pathologists in the analytical and postanalytical phases of IHC testing. This paper is the first of a 4-part series, under the general title of "Evolution of Quality Assurance for Clinical Immunohistochemistry in the Era of Precision Medicine."